Observation of the K + → π + ν ν ¯ $$ K^{+}→ π^{+}ν \overline{ν} $$ decay and measurement of its branching ratio - The NA62 collaboration; E. Cortina Gil; J. Jerhot; N. Lurkin; T. Numao; B. Velghe; V. W. S. Wong; D. Bryman; Z. Hives; T. Husek; K. Kampf; M. Kolesar; et al. (Journal of High Energy Physics)
Abstract A measurement of the K + → π + ν ν ¯ $$ K^{+}→ π^{+}ν \overline{ν} $$ decay by the NA62 experiment at the CERN SPS is presented, using data collected in 2021 and 2022. This dataset was recorded, after modifications to the beamline and detectors, at a higher instantaneous beam intensity with respect to the 2016–2018 data taking. Combining NA62 data collected in 2016–2022, a measurement of B K + → π + ν ν ¯ = 13.0 − 3.0 + 3.3 × 10 − 11 $$ \mathcal{B}\left(K^{+}→ π^{+}ν \overline{ν}\right)=\left({13.0}_{-3.0}^{+3.3}\right)× {10}^{-11} $$ is reported. With 51 signal candidates observed and an expected background of 18 − 2 + 3 $$ {18}_{-2}^{+3} $$ events, B K + → π + ν ν ¯ $$ \mathcal{B}\left(K^{+}→ π^{+}ν \overline{ν}\right) $$ becomes the smallest branching ratio measured with a signal significance above 5σ.